2005
DOI: 10.1590/s1516-35982005000500011
|View full text |Cite
|
Sign up to set email alerts
|

Herdabilidade e tendência genética para as produções de leite e de gordura em rebanhos da raça Holandesa no estado do Rio Grande do Sul

Abstract: RESUMO -Com o objetivo de estimar a herdabilidade e a tendência genética para as características produção de leite (PL), produção de gordura (PG) e porcentagem de gordura (%G), foram estudados registros de produção à primeira lactação de 5.007 vacas da raça Holandesa, filhas de 930 touros, pertencentes a 33 rebanhos criados no estado do Rio Grande do Sul entre 1984 e 1998. Para estimar as herdabilidades e predizer os valores genéticos dos indivíduos (VGs) para PL, PG e %G, foi utilizado um modelo animal consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…The heritability coefficient for lactation milk yield estimated in the present study (0.42) was higher than that observed in many studies. Muir et al (2004) estimated a heritability coefficient of 0.45 for milk yield in the Holstein breed, while Bolignon et al (2005) observed a value of 0.30, and Weber et al (2005) observed a value of 0.22, both also for milk yield in Holstein. Roman et al (2000) observed a heritability coefficient of 0.18 for milk yield in the Jersey breed.…”
Section: Productive and Reproductive Data Analysismentioning
confidence: 93%
“…The heritability coefficient for lactation milk yield estimated in the present study (0.42) was higher than that observed in many studies. Muir et al (2004) estimated a heritability coefficient of 0.45 for milk yield in the Holstein breed, while Bolignon et al (2005) observed a value of 0.30, and Weber et al (2005) observed a value of 0.22, both also for milk yield in Holstein. Roman et al (2000) observed a heritability coefficient of 0.18 for milk yield in the Jersey breed.…”
Section: Productive and Reproductive Data Analysismentioning
confidence: 93%
“…Durães et al (2001) trabalharam com rebanho Holandês no estado de Minas Gerais e encontraram ganhos genéticos para a característica de produção de leite de 18,4 kg ano -1 , uma das justificativas descritas pelos autores foi a baixa ênfase para as características de produção na escolha dos reprodutores, limitando o progresso genético do rebanho analisado. Boligon et al (2005) trabalharam com vacas Holandesas no estado do Rio Grande do Sul e encontraram progresso genético anual de 9,51 kg. Nos estudos de Balieiro et al 2000, encontraram ganho genético nas vacas da raça Gir Leiteiro de 10,46 kg ano -1 e, para os touros, o ganho genético foi de 19,29 kg ano -1 .…”
Section: Resultsunclassified
“…The genetic improvements in the direct selection for milk production advance much more than the improvements in the production of the constituents and, therefore, when we deal with the production of constituents as a percentage, we have a reduction. Boligon et al (2005) report a negative genetic correlation between milk yield and fat percentage, that is, the increase in milk production is not accompanied by an increase in milk fat content.…”
Section: Breedmentioning
confidence: 99%
“…In addition, this trait correlates with other important productive and functional traits in the production system, so the direct selection applied to milk production can produce indirect selection for other correlated traits, such as milk fat and protein percentages (Boligon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%